Implementation of Restorative Justice by the Semarang Police Criminal Investigation Unit to Criminal Perpetrators during the Investigation and Prosecution Stages - Melandri, Marco; Utari, Indah Sri; Rodiyah, Rodiyah (Fox Justi : Jurnal Ilmu Hukum, 2025)
This study examines the application of restorative justice by the Semarang City Police Criminal Investigation Unit (Satreskrim) in handling perpetrators of criminal acts during the stages of investigation and inquiry. The study arises from the need for alternative solutions to criminal cases that prioritize not only punishment but also the restoration of conditions for victims, offenders, and the wider community. The research is directed toward two central problems: first, how restorative justice is applied by the Semarang City Police, and second, what factors support or hinder its implementation. Using a juridical-sociological approach with descriptive analytical methods, this study relies on both primary and secondary data. Primary data were collected through interviews with police officers, victims, perpetrators, and community leaders involved in the settlement process. Secondary data were obtained from laws, regulations, literature, and previous studies. Data were analyzed qualitatively through reduction, presentation, and conclusion, guided by Howard Zehr and John Braithwaite’s restorative justice theory as well as Soerjono Soekanto’s theory of legal effectiveness. Findings reveal that restorative justice is implemented primarily through mediation, where perpetrators, victims, families, and community representatives meet to achieve peaceful agreements. These agreements generally consist of apologies, compensation, and case dismissal as regulated in Police Regulation Number 8 of 2021. Supporting factors include a clear legal foundation, institutional support, adequate facilities, and strong traditions of deliberation in society. Nevertheless, challenges remain, such as limited officer comprehension, differing views with prosecutors, weak regulatory enforcement, and public preference for retributive justice. The study concludes that restorative justice has shown positive results but requires stronger regulations, capacity building, and wider public education for consistent application.